2010
DOI: 10.1001/archinternmed.2009.545
|View full text |Cite|
|
Sign up to set email alerts
|

Food Price and Diet and Health Outcomes

Abstract: Background Despite surging interest in taxation as a policy to address poor food choice, US research directly examining the association of food prices with individual intake is scarce. Methods This 20-year longitudinal study included 12,123 respondent days from 5,115 participants in the Coronary Artery Risk Development in Young Adults (CARDIA) Study. Associations between food price, dietary intake, overall energy intake, weight, and HOMA insulin resistance (HOMA-IR) scores were assessed using conditional log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
114
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 41 publications
12
114
1
1
Order By: Relevance
“…In addition, one study found that a strict budget might affect parents' choices for purchasing from FF restaurants (30). Duffy et al showed that imposing taxes on high-calorie foods such as pizza had an impact on reducing consumption (45). The reduction of the price of healthy foods in low income communities was also effective in reducing the consumption of unhealthy foods (46).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one study found that a strict budget might affect parents' choices for purchasing from FF restaurants (30). Duffy et al showed that imposing taxes on high-calorie foods such as pizza had an impact on reducing consumption (45). The reduction of the price of healthy foods in low income communities was also effective in reducing the consumption of unhealthy foods (46).…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations for physical activity levels are issued by most governments as part of public health measures (Pate, Pratt, Blair, & Al., 1995). However, they tend to be updated frequently or adjusted due to external circumstances, such as changes in diet and food pricing (Duffey, Gordon-Larsen, Shikany, Guilkey, & Al., 2010), sedentary lifestyle (Martinez-Gonzalez, 1999), technology (Kautiainen, Koivusilta, Lintonen, Virtanen, & Rimpela, 2005), the built environment (Saelens, Sallis, Black, & Chen, 2003), family structure (Lissau & Sorensen, 1994) and social influences (Mcferran, Dahl, Fitzsimons, & Morales, 2010). Consequently, it has become increasingly important, from a public health policy-makers perspective, to develop reliably measuring physical activity intensity to ground public health guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence demonstrates the effect, or likely effect, of taxes on SSB consumption (3,(22)(23)(24)(25)(26)(27)(28)(29). Several studies, most focused on soda/soft drinks, have documented associations between higher SSB prices and lower consumption.…”
mentioning
confidence: 99%
“…Several studies, most focused on soda/soft drinks, have documented associations between higher SSB prices and lower consumption. Authors have utilized various methods, including observational data on food prices and consumption (22,26), household survey data on food purchases (23,(27)(28)(29), and experimental studies (25). A 2009 systematic review of food price elasticities found a price elasticity of demand of -0.79 (95% CI 0.33, 1.24) for soft drinks, estimated from 14 different studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation